Aminoglycosides and Capreomycin in the Treatment of Multidrug-resistant Tuberculosis: Individual Patient Data Meta-analysis of 12 030 Patients From 25 Countries, 2009-2016 - Cegielski, J Peter; Chan, Pei-Chun; Lan, Zhiyi; Udwadia, Zarir F; Viiklepp, Piret; Yim, Jae-Joon; Menzies, Dick (Clinical infectious diseases, 2021)
As new drugs are developed for multidrug-resistant tuberculosis (MDR-TB), the role of currently used drugs must be reevaluated. We combined individual-level data on patients with pulmonary MDR-TB published during 2009-2016 from 25 countries. We compared patients receiving each of the injectable drugs and those receiving no injectable drugs. Analyses were based on patients whose isolates were susceptible to the drug they received. Using random-effects logistic regression with propensity score matching, we estimated the effect of each agent in terms of standardized treatment outcomes. More patients received kanamycin (n = 4330) and capreomycin (n = 2401) than amikacin (n = 2275) or streptomycin (n = 1554), opposite to their apparent effectiveness. Compared with kanamycin, amikacin was associated with 6 more cures per 100 patients (95% confidence interval [CI], 4-8), while streptomycin was associated with 7 (95% CI, 5-8) more cures and 5 (95% CI, 4-7) fewer deaths per 100 patients. Compared with capreomycin, amikacin was associated with 9 (95% CI, 6-11) more cures and 5 (95% CI, 2-8) fewer deaths per 100 patients, while streptomycin was associated with 10 (95% CI, 8-13) more cures and 10 (95% CI, 7-12) fewer deaths per 100 patients treated. In contrast to amikacin and streptomycin, patients treated with kanamycin or capreomycin did not fare better than patients treated with no injectable drugs. When aminoglycosides are used to treat MDR-TB and drug susceptibility test results support their use, streptomycin and amikacin, not kanamycin or capreomycin, are the drugs of choice.